"I realised it weren't about spending the money. It's about doing something together:" the role of money in a community empowerment initiative and the implications for health and wellbeing. (September 2020) - Townsend, A.; Abraham, C.; Barnes, A.; Collins, M.; Halliday, E.; Lewis, S.; Orton, L.; Ponsford, R.; Salway, S.; Whitehead, M.; Popay, J.
Abstract: Community initiatives aiming to reduce health inequalities are increasingly common in health policy. Though diverse many such initiatives aim to support residents of disadvantaged places to exercise greater collective control over decisions/actions that affect their lives - which research suggests is an important determinant of health – and some seek to achieve this by giving residents control over a budget. Informed by theoretical work in which community capabilities for collective control are conceptualised as different forms of power, and applying a relational lens, this paper presents findings on the potential role of money as a mechanism to enhance these capabilities from an on-going evaluation of a major place-based initiative being implemented in 150 neighbourhoods across England:The Big Local (BL). The research involved semi-structured interviews with 116 diverse stakeholders, including residents and participant observation in a diverse sample of 10 BL areas. We took a thematic constant comparative approach to the analysis of data from across the sites. The findings suggest that the money enabled the development of capabilities for collective control in these communities primarily by enhancing connectivity amongst residents and with external stakeholders. However, residents had to engage in significant 'relational work' to achieve these benefits and tensions around the money could hinder communities' 'power to act'. Greater social connectivity has been shown to directly affect individual and population health by increasing social cohesion and reducing loneliness. Additionally, supporting enhanced collective control of residents in these disadvantaged communities has the potential to improve population health and reduce health inequalities. Highlights: Supporting communities in gaining collective control has potential to reduce health inequities. Disadvantaged communities with control over money, can develop 'powers' to improve where they live. Communities in ' total ' collective control of budgets could benefit in symbolic and monetary ways. Local initiatives require varied relational work in order to achieve positive community benefits. Local resident led initiatives need to recognize, the exercise of relational work in their design.